Trainee psychotherapy effectiveness at a psychodynamic training clinic: a practice-based study. Issue 1 (2nd January 2019) - Paine, David R.; Bell, Chance A.; Sandage, Steven J.; Rupert, David; Bronstein, Miriam; O'Rourke, Christopher G.; Stavros, George S.; Moon, Sarah H.; Kehoe, Lauren E.
Abstract : The degree to which clinical experience is a significant factor in predicting positive psychotherapeutic outcomes is an open question. Empirical studies comparing experienced and beginning practitioners on differences in client outcomes have yielded mixed results. While multiple sources have indicated that trainees are generally effective therapists, few of these studies have examined the effectiveness of graduate-level therapists in a psychodynamic training program. In this study, conducted in the United States, we use a practice-based research approach to examine the outcomes of clients working with trainees at a community mental health clinic in the northeast United States. The theoretical orientation identified by the clinic and training program is psychodynamic with an interpersonal and/or relational emphasis. Results indicated that clients working with trainees at this clinic demonstrated improvement across several indicators of symptoms and psychosocial functioning over the time they received treatment. Implications for training and service reimbursement are discussed.